Operational cost comparison of alternative fuel vehicles for public transportation - Mercado, Jose Gabriel; Quiros, Edwin
This paper presents the operational cost analysis of different alternative fuel vehicles used for Public Utility Jeepneys (PUJs) in Metro Manila. Four models were generated using data from the UP-SM North Jeepney route. Model A used actual data gathered from the on-road tests conducted. Model B did not consider the downtime days to normalize the daily net income. Model C kept the costs not related to fuel and maintenance, jeepney fare, and data influence by the preference of the driver, constant. Model D assumed only jeepney type varied, without accounting for any preference mentioned in Model C. For all models, in terms of Fuel Cost (PhP) per Passenger-km, the Electric Jeepney is 35-49% more economical and has 1%-36% higher net income vs Diesel Jeepney. However, the LPG jeepney is less economical by 8%-18% vs Diesel Jeepney in Models A-C but more economical by 4% in Model D due to higher cost of Diesel fuel. In terms of Net Income (PhP) per Passenger-km, LPG Jeepney has 10% lower income vs Diesel Jeepney in Models A&B but has 5% higher income in Models C&D as considered days are the same, thereby minimizing differences in the number of passengers that affects both parameters.
Keywords: Jeepney; Alternative fuels; Operational cost analysis